Revision of Fauveliopsidae Hartman, 1971 (Annelida, Sedentaria) - Salazar-Vallejo, Sergio I.; Zhadan, Anna E.; Rizzo, Alexandra E. (Zootaxa, 2019)
Abyssal polychaetes are usually difficult to be identified because they are small, their body patterns differ from their shallow water relatives, their delicate bodies are often damaged during sampling and sieving, and their taxonomy is in need of revision. Members of the family Fauveliopsidae Hartman, 1971 are widespread in deep ocean basins and they follow the above statements. In this contribution, we present a revision of all available type and non-type material for the family. Our objective is to provide keys to identify genera and species, as well as standardized diagnoses, and illustrations for most species, excluding those described since 2011, or where type material was not available. One genus, Riseriopsis n. gen., is proposed and four species are newly described. The Fauveliopsidae now includes 24 species in three genera: Fauveliopsis McIntosh, 1922 (13 species), Laubieriopsis Petersen, 2000 (8 species), and Riseriopsis n. gen. (3 species). Fauveliopsis includes species usually living inside gastropod or scaphopod shells or foraminiferan tubes, Laubieriopsis and Riseriopsis include species commonly regarded as free living, although some species of the latter have very long bodies and have been found inside soft tubes. Fauveliopsis includes: F. adriatica Katzmann & Laubier, 1974, F. armata Fauchald & Hancock, 1981, F. brattegardi Fauchald, 1972a, F. brevipodus Hartman, 1971, F. challengeriae McIntosh, 1922, F. glabra (Hartman in Hartman & Barnard, 1960), F. jameoaquensis Núñez in Núñez, Ocaña & Brito, 1997, F. levensteinae n. sp., F. magalhaesi n. sp., F. magna Fauchald & Hancock, 1981, F. olgae Hartmann-Schröder, 1983, F. rugosa Fauchald, 1972b, and F. scabra Hartman & Fauchald, 1971. Laubieriopsis includes: L. arenicola (Riser, 1987), L. blakei n. sp., L. brevis (Hartman, 1965), L. cabiochi (Amoureux, 1982), L. fauchaldi (Katzmann & Laubier, 1974) n. comb., L. hartmanae (Levenstein, 1970) reinst., L. norvegica Zhadan & Atroshchenko, 2012, and L. petersenae Magalhães, Bailey-Brock & Rizzo, 2014. Riseriopsis includes: R. arabica (Hartman, 1976) n. comb., R. confusa (Thiel, Purschke & Böggemann, 2011) n. comb., and R. santosae n. sp. Keywords. Deep-sea species, taxonomy, genital papillae, genera, species Introduction The family-group name Fauveliopsidae was established by Hartman (1971) and derived from Fauveliopsis McIntosh, 1922. The genus-group name was dedicated to Pierre Fauvel, famous French polychaetologist, and the type species, F. challengeriae McIntosh, 1922, was described based on specimens collected during the HMS Challenger expedition. The phylogenetic affinities of fauveliopsids are unsettled in part due to the fact that only a few species have been included in past analyses; after the analysis of morphological and molecular characters (Zrzavý et al. 2009, figure 6), Fauveliopsidae groups with Cossuridae and Paraonidae, as a sister group to what has been regarded as Cirratuliformia (Cirratulidae, Acrocirridae, Flabelligeridae). This family includes benthic species that are rarely abundant, and they tend to prefer silty bottoms. Most species have been described from deep-sea locations including trenchs (Menzies & George 1967); however, a few shallow water species were described from the Canary Islands (5 m), New Zealand (20 m), and the Adriatic Sea (60 m). Members of the family are free living or find shelter in tubes of cemented silt grains (Blake & Petersen 2000, Petersen 2000); they can also be found inside scaphopod, or gastropod mollusk shells, or inside tubular foraminiferans (Bathysiphon Sars, 1872). It should be noted, however, that typical Bathysiphon tests include sponge spicules, and that Psammosiphonella Avnimelech, 1952 was proposed for those agglutinated foraminiferans whose tests do not include sponge spicules; this latter genus has been regarded as distinct (Rögl 1995; Kaminski 2004; Kaminski et al. 2009). This is relevant because at least in some cases, as we show below, fauveliopsid tubes have a complex organization, such that other interpretations might be involved. Another interesting issue is that Małecki (1973) regarded these foraminiferan tests (Bathysiphon and Psammosiphonella) as polychaete tubes, because they lack the characteristic basal embryonic chamber, proloculus, which define foraminiferans. This idea was not followed and the above genera are still regarded as foraminiferans (Kaminski 2004). Fauveliopsid bodies are subcylindrical, wider medially, or club-shaped; in the latter, the anterior region is the narrower one. Parapodia are displaced dorsally with notopodia being clearly dorsolateral, whereas neuropodia are lateral and chaetae are directed anteriorly, usually along anterior region, and it is related to free living species. The combination of a usually posterior wider region and the parapodial disposition, together with the presence of some anal papillae has made it difficult to assess body polarity and for some descriptions the body ends were incorrectly characterized (Laubier 1972:698; Hartman 1976:236, Fig. 12a). There are four morphological traits of typical polychaete body patterns that can explain this difficulty: 1) anterior region is wider than the rest of the body; 2) segments are less clear cut anteriorly; 3) chaetal bundles are displaced to the anterior border of each chaetiger, being displaced to the median region and eventually towards the posterior region in median to posterior chaetigers; and 4) chaetae are directed anteriorly in a few anterior chaetigers, and towards the posterior region in the rest of the body. Surprisingly, these patterns are reversed among fauveliopsids because many have evolved to live within tubes, bending their bodies obliquely or ventrally, and by directing their chaetal bundles anteriorly (originally noticed by McIntosh 1922:6). These modifications could provide better anchoring for chaetae and parapodia. Inside gastropod shells, there are different conditions for what lies dorsally or ventrally; this might have selected for body modifications. For example, parapodia become dorsally displaced and this would enlarge ventral and lateral surface areas to be in close contact with the shell. Katzmann & Laubier (1974:10, Fig. 3C) showed that in some fauveliopsids the narrower region is exposed through the shell aperture. Blake & Petersen (2000) clarified the body end confusion, standardized concepts about morphological features, and redescribed some species. However, earlier descriptions deserve re-evaluation because of a potential confusion of body ends. Riser (1987) provided some histological details and indicated that stomach contents consisted of foraminiferans and silt, whereas Purschke (1997) made SEM illustrations of nuchal organs. Hartman (1971:1411) proposed Fauveliopsidae to include four genera that she regarded as flabelligerid-like: Bruunilla Hartman, 1971, Fauveliopsis, Flabelligella Hartman, 1965, and Flota Hartman, 1967. In a subsequent publication, Hartman (1974:199, 235) apparently changed her perspective and transferred Fauveliopsis to the Flabelligeridae; however, in a posthumous publication (Hartman 1978:175) she used the family as originally proposed. The composition of the Fauveliopsidae has been modified over the years, with Orensanz (1974) transferring Flabelligella to Acrocirridae, Pettibone (1979) indicating that Bruunilla belongs in Polynoidae, and Buzhinskaja (1996) proposing an independent family for Flota. For the latter genus group name, Salazar-Vallejo & Zhadan (2007) regarded it as a junior synonym of Buskiella McIntosh, 1885. The family was thus restricted to Fauveliopsis but it now also includes Laubieriopsis Petersen, 2000 and Riseriopsis n. gen. Three major publications have addressed identification problems in Fauveliopsis. Katzmann & Laubier (1974) prepared a key to species based upon the number of chaetigers, integument features and type of chaetae throughout body. Amoureux (1982) compiled the known species and pointed out their number of chaetigers. Hartmann-Schröder (1983) had a different approach and relied more on chaetal patterns than on number of chaetigers. Because body ends were confused in some of the original descriptions, the species deserve reinterpretation. In order to standardize the morphological features, the diagnoses below combine these approaches and additional observations based upon specimens with some remarks about the match between previous descriptions and these standardized diagnoses, as made elsewhere for tropical American species (Salazar-Vallejo 2009). In this contribution, we have dealt with all material available of fauveliopsid genera and species. We propose a new genus, Riseriopsis n. gen., to include two species of Fauveliopsis provided with long, posteriorly swollen bodies, with long segments along median region, and two known species are newly combined. Further, four species are newly described, and another one, Laubieriopsis hartmanae (Levenstein, 1970), is redescribed and reinstated.